Quantification of d- and l-2-Hydroxyglutarate in Drosophila melanogaster Tissue Samples Using Gas Chromatography-Mass Spectrometry - Li, Hongde (Methods Mol Biol, 2019)
The fruit fly Drosophila melanogaster has emerged as an ideal system in which to study 2-hydroxyglutarate (2HG) metabolism. Unlike many mammalian tissues and cell lines, which primarily accumulate d- or l-2HG as the result of genetic mutations or metabolic stress, Drosophila larvae accumulate high concentrations of l-2HG during normal larval growth. As a result, flies represent one of the few model systems that allows for studies of endogenous l-2HG metabolism. Moreover, the Drosophila genome not only encodes key enzymes involved in the synthesis and degradation of d-2HG, but the fly has also been used as to investigate the in vivo effects of oncogenic isocitrate dehydrogenase 1 and 2 (IDH1/2) mutations. All of these studies, however, rely on mass spectrometry-based methods to distinguish between the d- and l-2HG enantiomers. While such approaches are common among labs studying mammalian cell culture, few Drosophila studies have attempted to resolve and measure the individual 2HG enantiomers. Here we describe a highly reproducible gas chromatography-mass spectrometry (GC-MS)-based protocol that allows for quantitative measurements of both 2HG enantiomers in Drosophila homogenates.